The 56-kilodalton major protein antigen of Rickettsia tsutsugamushi: molecular cloning and sequence analysis of the sta56 gene and precise identification of a strain-specific epitope. - Stover, C K (1990)
Lasting immunity against Rickettsia tsutsugamushi, the causative agent of scrub typhus fever, has been demonstrated to be strain specific. Two protein antigens of 110 and 56 kilodaltons (kDa) have been shown to exhibit strain-specific epitopes. The 56-kDa scrub typhus antigen (Sta56) is an abundant outer membrane protein of R. tsutsugamushi and is an antigen often recognized by humans infected with this obligate intracellular bacterium. In this study the complete gene encoding Sta56 (strain Karp) was cloned into pBR322 on a 2.3-kilobase genomic HindIII DNA fragment and the complete 56-kDa polypeptide was expressed in Escherichia coli. DNA sequence analysis of the 2.3-kilobase HindIII fragment revealed an open reading frame large enough to encode a 56-kDa polypeptide. A putative signal sequence was identified at the deduced amino terminus of the Sta56 polypeptide, and pulse-chase analysis of maxicells labeled with [35S]methionine demonstrated that a higher-molecular-weight precursor matures into the 56-kDa polypeptide. Epitope scanning analysis with synthetic peptides derived from the deduced amino acid sequence identified an octapeptide (located from amino acid residues 117 to 124) that was reactive with a Karp strain-specific monoclonal antibody (K13F88A). Other epitopes recognized by different monoclonal antibodies, including another Karp strain-specific monoclone (K1E106), were localized to different regions of the protein based on their reactivities with lambda gt11 recombinants expressing various portions of the sta56 gene.